INFORMATION SERVICES AIR TICKETS BOOKING FACILITY THROUGH INTERNET USING PHP AND MYSQL - R. Muji hemi Priatna; Ir. Fitri Sjafrina, MM (Jurnal Sistem Informasi, 2006)
Currently Tourism Raudhah still use traditional management in doing ministry. Theauthor therefore tried to create a media to convey and disseminate information aboutproducts and services. Raudhah tour, about the company profile, schedules -timetables and various services provided by the company in a website. Internet is onealternative means of promotion for travel agents air transportation, tourism raudhah.To compete in world business trip air transportation. Website as a media campaignwill provide some value plus the promotional tools with international scope that canbe accessed by anyone in the world via the internet and can display a much morecomplete information with promotional costs are relatively lower compared to otherpromotional media.